Premature Birth with Complicated Perinatal Course Delaying Diagnosis of Prader-Willi Syndrome - G. Ciana; M. C. Fertz; V. Pecile; S. Demarini (Hindawi Limited, 2011)
Prader-Willi syndrome in the newborn is essentially characterized by marked hypotonia, feeding difficulties, hypogonadism, and possible characteristic facial features. However, diagnosis at this age may be particularly difficult, and dysmorphic features may be subtle or absent. Prematurity can furthermore delay clinical features recognition and typical complications due to preterm birth may contribute to divert the diagnosis. We describe a preterm baby with a complicated perinatal course later diagnosed as PWS.